PEMBUATAN PAVING BLOCK DENGAN SERBUK BATU KARANG SEBAGAI SUBSTITUSI SEMEN MENGGUNAKAN METODE DRYMIX - Rochmanto, Decky; Pratama, Andrie Mandala Yudha; Saputro, Yayan Adi; Qomaruddin, Mochammad; Roesdiana, Tira (Universitas PGRI Semarang, 2023)
Utilizing dead rock as a cement additive in the manufacture of paving blocks, and the rock contains CaCO3 which includes limestone as in the content of cement which has lime content (CaO), the aim is to determine the effect of rock on the compressive strength value of paving blocks. Utilization of stone in the manufacture of paving blocks using a mixture of design 0%, 5%, 10%, and 15% of the weight of cement to be used. Manufacture of paving blocks using a ratio of 1: 3 sand cement, cement water factor 0.4 with molds 20 x 10 x 6 cm, compaction weight of 1 paving 3.52 kg and testing compressive strength at 7, 14 and 28 days, using the method (SNI 03- 0691-1996) paving block. From the analysis of compressive strength testing, it was found that the compressive strength of paving blocks increased towards normal paving blocks to produce the highest compressive strength with added rock in the 15% variation at the age of 28 days, which amounted to 45.1 MPa and included the quality of class A paving blocks with SNI 03-0691 (1996) standards. The compressive strength of the 5% variation at 28 days of age is 38.7 MPa and the compressive strength of the 10% variation at 28 days of age is 43.5 MPa. It can be seen that coral stone as a cement additive is able to improve the quality of compressive strength of paving blocks.